Familientradition Hartz IV? Soziale Reproduktion von Armut in Familie und Biografie - Wagner, Dominik (Rekonstruktive Forschung in der Sozialen Arbeit, 2017)
The study addresses the question of how the biographies of people whose families remain in poverty for generations are structured. In addition, it provides detailed insights into the life of families in relation to ALG II and reconstructively traces the individual context of social reproduction of poverty. It turns out that the way the families interviewed deal with poverty depends on a multitude of interwoven biographical structural aspects.